HEADMASTER EVALUATION OF TEACHER PERFORMANCE IMPROVEMENT IN MADRASAH ALIYAH SWASTA (MAS) AL MA’ARIF JIKOTAMO - Lasuhu, Abdul Rauf (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The evaluation of the madrasah head as a leader and manager becomes a key factor in building a productive educational atmosphere. The intellectual, emotional, spiritual, and social abilities of the madrasah head have a significant impact on their leadership effectiveness. This study focuses on the evaluation of the madrasah head at Al Ma'arif Jikotamo Private Islamic Senior High School (MAS). This research uses a qualitative method approach. The research location is at Al Ma'arif Jikotamo Private Islamic Senior High School in South Halmahera Regency. The data sources for this research are the educators present at Al Ma'arif Jikotamo Private Islamic Senior High School in South Halmahera Regency. Data collection techniques include observation, documentation, and interviews. Data processing techniques used include editing, coding, and tabulation. The data analysis includes data reduction, data presentation, and data verification. The results of the research show that the evaluation in this madrasah has been effective, as seen from the good performance of the madrasah head as well as management's openness in interacting with teachers. Good collaboration and communication between the madrasah head and teachers, along with well-organized activities characterize this educational environment. The performance of educators at MAS Al Ma'arif Jikotamo is also assessed to be satisfactory based on effective teaching methods and positive interaction between teachers and students. The quality teaching by teachers and good behavior patterns create a comfortable learning environment for students which reflects real efforts to achieve quality education goals at secondary school level.